Pengaruh Promosi Online, Desain Kemasan, dan Inovasi Produk Terhadap Keputusan Pembelian Pada UMKM Keripik Tempe A-Syifa Manisrenggo Kota Kediri - ; Suwasono, Edy; Sutapa, Heru (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to determine the influence of online promotions, packaging design and product innovation on purchasing decisions in MSMEs of A-syifa Manisrenggo Tempe Chips, Kediri City. The variables in this research are Online Promotion (X1), Packaging Design (X2), Product Innovation (X3), and Purchase Decision (Y). The location of this research is the UMKM Tempe Chips A-syifa Manisrenggo, Kediri City. Data collection techniques include interviews, observation, literature study, and questionnaires. The number of samples in this study was 94 respondents. The analysis used uses quantitative methods with SPSS version 22 software program analysis. The analysis techniques used are validity test, reliability test, linearity test, classical assumption test, multiple linear regression analysis, t test (partial), f test (simultaneous), and coefficient of determination. Based on the results of multiple linear regression statistical tests in this research, it shows that there is an influence between Online Promotion (X1), Packaging Design (X2), and Product Innovation (X3) simultaneously on Purchasing Decisions (Y). These results can be seen from Sig. F is 0.000 < 0.05 which means that Ha is accepted and Ho is rejected. It is known that the coefficient of determination R2 is 0.539 or 53.9%. These results show that the contribution of the independent variable to the dependent variable is 53.9% and the remaining 46.1% is influenced by other variables not examined in this research.